Diagnóstico socioeconômico e ambiental da lagoa do Apodi-RN - Soares, Lorena Lívina Lima Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
This work aims to diagnose the socioeconomic and environmental situation around the Apodi-RN Lagoon, as well as to identify the implications on the quality of life of the riverside populations, located in the Malvinas neighborhood of Apodi. As a methodological procedure, a semi-structured questionnaire was used with questions about the socioeconomic profile of the interviewee, components of aspects of environmental sanitation and environmental perception. 185 interviews were carried out during the months of February to May 2017. Residuals and effluents from residential sewage have several impacts on the environment, leading to serious problems related to population health and the degradation of natural resources. In addition, it was verified that most of the individuals are inserted in a medium of socioeconomic vulnerability. The population as one of the main agents of pollution of the lagoon pointed out the realization of cultural events. According to the interviewees, the Apodi lagoon is contaminated, the population recognizes this type of pollution, but it is used for various activities, including fishing and agriculture. Thus, the Apodi Lagoon has its environmental condition compromised and it is necessary to adopt mitigating measures with the purpose of promoting sustainable development and reversing the current level of environmental degradation.
Keywords: Degradação dos Recursos Hídricos; Degradation of Water Resources; Percepção Ambiental; Environmental Perception; Vulnerabilidade Socioeconômica; Socioeconomic Vulnerability; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA